Transform () = 3( + 2)
2 + 1 in the form () =
2 + + and find the
vertex.
Complete the process below by filling out the blanks in each step.
Solution: () = 3( + 2)2 + 1
() = 3( + 2)( + 2) + _____
() = 3 (2 + ______ + ____) +1
() = 32 + 12 + 12 + 1
() = 32 + 12 + _____
Vertex ( ____, _____)


Transform 3 2 2 1 In The Form 2 And Find The Vertex Complete The Process Below By Filling Out The Blanks In Each Step Solution 3 22 1 3 2 2 3 2 1 32 12 12 1 32 class=

Sagot :

Answer:

8

8

8

8the 8 feel so faith

8

Step-by-step explanation:

acebbko

Answer:

f(x) = 3(x + 2)² + 1

f(x) = 3(x + 2)(x + 2) + 1

f(x) = 3(x² + 4x + 4 ) + 1

f(x) = 3x² + 12x + 12 + 1

f(x) = 3x² + 12x + 13

Vertex ( -2 , -17 )

x-vertex:

-b/2a = -12/ 2(3) = -12/6 = -2

y-vertex:

= 3x² + 12x + 13

= 3(-2) + 12(-2) + 13

= -6 - 24 + 13

= -30 + 13

= -17

Pabrainliest, thanks:)